Analysis of Fibonacci Sequence on Violet Flower’s Petals - Fauzi, Nur Farisya Syafiqah; Muhammad Basri, Cik Sri Mazzura (Enhanced Knowledge in Sciences and Technology, 2022)
This project focuses on the Fibonacci sequence and the Golden Ratio to analyze the violet flower’s petals. Fibonacci sequence commonly found in everyday lives either in nature such as animals and plants or in infrastructure itself that occurs naturally. Fibonacci numbers are inextricably linked to the golden ratio: Binet's formula expresses the nth Fibonacci number in terms of n and the golden ratio, and it indicates that as n increases, the ratio of two consecutive Fibonacci numbers goes to the golden ratio. By applying the Fibonacci sequence, we can analyze the violet flower’s petals to create a visual design by using MATLAB software.